Monitoring the Remineralization of Early Simulated Lesions using a pH Cycling Model with CP-OCT - Kang, Hobin (2013)
If caries lesions are detected early enough they can be arrested by chemical intervention and dietary changes without the need for chemical intervention. Optical coherence tomography is ideally suited to monitor the changes that occur in caries lesions as a result of nonsurgical intervention, since OCT can nondestructively image the internal structure of the lesion. One of the most important changes that occurs in a lesion is preferential deposition of mineral in the outer surface zone. The deposition creates a highly mineralized and weakly scattering surface zone that is clearly visible in OCT images. Since this zone is near the highly reflective surface it is necessary to use cross-polarization OCT imaging to resolve this zone. Several CP-OCT studies have been conducted employing different remineralization models that produce lesions with varying mineral gradients. Previous studies have also demonstrated that automated algorithms can be used to assess the lesion depth and severity even with the presence of the weakly reflective surface zone. In this study we investigated the remineralization of lesions of varying severity using a pH cycling remineralization model and the change of the lesion was monitored using CP-OCT. Although the lesion depth and severity decreased after remineralization, there was still incomplete remineralization of the body of the lesion.